Collagenous colitis: jejunal and colorectal pathology. Issue 9 (September 1992) - Armes, J; Gee, D C; Macrae, F A; Schroeder, W; Bhathal, P S
Abstract : AIMS: To determine: (1) whether there is an association between collagenous colitis and coeliac disease or lymphocytic colitis; (2) the distribution of lymphocyte subsets and macrophages in the lamina propria and surface epithelial layer in collagenous colitis; and (3) the colorectal distribution of the disease and whether a mucosal biopsy specimen, using a flexible sigmoidoscope, is sufficient to diagnose it. METHODS: The clinical data and colorectal biopsy specimens from 38 patients with collagenous colitis were studied. In 10, small bowel biopsy specimens were also available for review. Immunostaining of the mucosal lymphoid infiltrate with a panel of relevant antibodies was carried out on formalin fixed tissue in seven cases; in three the phenotyping was performed on fresh biopsy specimens separately frozen or fixed in B5 solution. RESULTS: Coeliac disease was found in four out of the 10 patients with collagenous colitis who had had a small bowel biopsy, in contrast to the prevalence of the disease in Australia of 1 in 3000. Collagenous colitis did not respond to gluten withdrawal. Five of 29 (17%) of the patients had a mixed pattern of lymphocytic and collagenous colitis. Immunostaining of the lymphoid infiltrate showed that the striking increase in intraepithelial lymphocytes in collagenous colitis was due to an influx of CD8 positive cells. The occurrence and severity of collagenous colitis along the large bowel were independent of the anatomical site, and in more than 90% of cases biopsy specimens from the sigmoid colon or rectum were diagnostic. CONCLUSIONS: There is a very high incidence of coeliac disease among patients with collagenous colitis so that jejunal biopsy should be an essential part of their investigations, especially if symptoms persist. However, only a minority showed a mixed pattern of lymphocytic and collagenous colitis. The intraepithelial lymphocytes in collagenous colitis are CD8 positive cells. Collagenous colitis can be diagnosed from rectal or sigmoid colon biopsy specimens in more than 90% of cases.